Elastic properties of additively manufactured steel produced with different scan strategies - Zinovieva, Olga S.; Romanova, Varvara A.; Zinoviev, A. V.; Nekhorosheva, O.; Balokhonov, Ruslan R. (International journal of mechanical sciences)
The current study reports the application of a novel integrated process-structure-property approach in laser powder bed fusion (LPBF) additive manufacturing of stainless steel, focused on the analysis of local stress fields and effective orientation-dependant elastic properties. Specifically, the finite difference method is applied for thermal simulations of the LPBF process at the melt pool scale. The calculated temperature data serve as an input for grain structure modelling with cellular automata. Microstructural information, including the grain geometry and crystallographic orientations, is taken explicitly into account in micromechanical finite element simulations. The study discusses the relationship between the process-induced microstructure and the anisotropic elastic response of LPBF 316L steel samples fabricated using uni- and bidirectional scanning. In addition, the contribution analyses the scan strategy impact on the incipience of plastic deformation in additively manufactured steel. Commonly for both types of samples, the elastic moduli have the least values when tension is applied along the scan direction. Local stress fields form a laminated-like pattern of alternating through-the-thickness layers of lower and higher stresses following the process-induced mesoscopic material structure. The results indicate that the crystallographic texture has a more substantial effect on the anisotropy of elastic properties than the laminated-like pattern of LPBF 316L steel. Comparing microstructure-based finite element simulations and analytical calculations based on the Voigt-Reuss-Hill scheme, this paper presents new evidence for the ability of the fast and simple analytical texture-based approach to give an accurate prediction of anisotropic elastic properties of additively manufactured materials.